PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS PETUALANGAN TERHADAP PENINGKATAN GERAK DASAR LOKOMOTOR - Aziz Haqqul Mubin; Endi Rustandi (Universitas Majalengka, 2021)
ABSTRACT. Basic locomotor movements are movements that cause the haste or skill used to move the body from one place to another. The research method is research and development. This research is a development that aims to produce a product in the form of an adventure-based learning model on locomotor basic motion at SDN 2 Panyingkiran Kidul. The sample in the small-scale study was 10 students and the large scale was 20 students. The data from the analysis of teacher evaluation data obtained an average proportion of 83.3% and expert evaluation of 80.6%. From the recap of the value of the questionnaire results that were filled in by 10 students in total, the average proportion was 90%, meaning that students could complete the exercise in a good category. The results of the small-scale trial recap were 2.5% who answered difficult, 25% who answered medium, and 72.5% who answered easy. The results of the large-scale trial data analysis of 20 students as a whole obtained an average proportion of 88%, meaning that students can complete the exercises in a good category. The results of the large-scale trial recap were 6.25% who answered difficult, 23.75% who answered medium, and 70% who answered easy. Thus, it can be denied that the development of an adventure-based learning model is acceptable and improves the basic locomotor movement abilities of students at SDN 2 Panyingkiran Kidul.Keywords: Model Development; Learning; Basic Locomotor movementsABSTRAK. Gerakan dasar lokomotor adalah gerakan yang menyebabkan terjadinya perpindahan tempat atau keterampilan yang digunakan memindahkan tubuh dari satu tempat ke tempat lainny. Metode penelitian ini adalah research and development. Penelitian ini merupakan pengembangan yang bertujuan menghasilkan produk berupa model pembelajaran berbasis petualangan pada gerak dasar lokomotor di SDN 2 Panyingkiran Kidul. Sampel dalam penelitian pada skala kecil 10 siswa dan skala besar 20 siswa.Data hasil analisis data evaluasi guru penjas didapat rata-rata persentase 83.3% sedangkan evaluasi dosen ahli 80.6%. Adapun dari rekap nilai hasil angket yang di isi oleh 10 siswa secara keseluruhan didapat rata-rata persentase 90% artinya siswa dapat menuntaskan latihan dengan kategori baik. Adapun hasil rekap angket uji coba skala kecil adalah adalah 2,5% yang menjawab sulit, 25% yang menjawab sedang, dan 72,5% yang menjawab mudah. Hasil analisis data uji coba skala besar 20 siswa secara keseluruhan didapat rata-rata persentase 88% artinya siswa dapat menuntaskan latihan dengan kategori baik. Adapun hasil rekap angket uji coba skala besar adalah adalah 6.25% yang menjawab sulit, 23.75% yang menjawab sedang, dan 70% yang menjawab mudah. Dengan demikian, dapat disimpulkan bahwa pengembangan model pembelajaran berbasis petualangan dapat diterima dan meningkatkan kemampuan gerak dasar lokomotor siswa di SDN 2 Panyingkiran KidulKata Kunci: Pengembangan Model; Pembelajaran; Gerak Dasar Lokomotor.